2018
DOI: 10.1016/j.cemconcomp.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate moisture state and roughness on interface microstructure and bond strength: Slant shear vs. pull-off testing

Abstract: There are conflicting views in the literature concerning the optimum moisture state for an existing substrate prior to the application of a repair material. Both saturated-surface-dry (SSD) and dry substrates have been found to be preferable in a variety of studies. One confounding factor is that some studies evaluate bonding of the repair material to the substrate via pull-off (direct tension) testing, while others have employed some form of shear specimens as their preferred testing configuration. Available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…Until now, it has been shown in literature on the basis of research that the mechanical treatment of the surface of the concrete substrate by shot-blasting improves the level of bonding of the cement mortar overlay with this substrate. [5][6][7] In turn, Silfwerbrand and Beushausen [8] , Silfwerbrand et al [9] and Sadowski et al [10] showed, based on tests, that the removal of the cement laitance from the surface of concrete substrate improves the level of bonding between the cement mortar overlay and the substrate. It is also known from literature that the use of a bonding agent on the surface of the substrate before the application of the overlay improves the level of the bonding between the cement mortar overlay and the concrete substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, it has been shown in literature on the basis of research that the mechanical treatment of the surface of the concrete substrate by shot-blasting improves the level of bonding of the cement mortar overlay with this substrate. [5][6][7] In turn, Silfwerbrand and Beushausen [8] , Silfwerbrand et al [9] and Sadowski et al [10] showed, based on tests, that the removal of the cement laitance from the surface of concrete substrate improves the level of bonding between the cement mortar overlay and the substrate. It is also known from literature that the use of a bonding agent on the surface of the substrate before the application of the overlay improves the level of the bonding between the cement mortar overlay and the concrete substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, unrealistic loading conditions are applied to the interface. The failure of the interface depends on the angle of the plane with respect to the load 3 . In addition, the test is relatively insensitive to the surface preparation and roughness, since bond failures occurred only for smooth surfaces [2,17].…”
Section: Influence Of Test Methods On Bond Strengthmentioning
confidence: 99%
“…Dry-type surface was reached by curing the substrate surface for 14 days at laboratory conditions of 23 ± 2, 55% ± 5% RH, as also seen in [3]. During the curing, surface substrate was covered with a plastic sheet, in order to…”
Section: Treatment Prior To Overlaymentioning
confidence: 99%
“…Bond test configuration designed by authors: (1) substrate, (2) overlay,(3) interface, (4) slip point measured by LDTV, (5) bearing plates, (6) loading device,(7) force transducer, (8) rigid support…”
mentioning
confidence: 99%
“…The whole range of possible moisture conditions expected in the field was taken into account in series investigated, in particular dry, 75% and SSD. Dry-type surface was reached by curing the substrate surface for 14 days at laboratory conditions of 23 ± 2, 55% ± 5% RH, as also seen in[3]. During the curing, surface substrate was covered with a plastic sheet, in order to slow down the carbonation process.…”
mentioning
confidence: 99%